Pengaruh Ukuran Perusahaan, Intensitas Modal dan Intensitas Persediaan terhadap Agresivitas Pajak - Ardiansyah, Riky; Fikriyah , Siti Hailatul (Jurnal Nusa Akuntansi, 2024)
This research aims to analyze the influence of Company Size, Capital Intensity, Inventory Intensity on Tax Aggressiveness. This type of research is quantitative with secondary data sources. The population in this research is industrial sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The sample selection method used in this research was purposive sampling so that the final sample obtained was 12 companies. The analysis technique used in this research uses multiple linear regression analysis techniques. The research results show that simultaneously the variables Company Size, Capital Intensity, Inventory Intensity influence Tax Aggressiveness. Then partially it shows that Company Size, Capital Intensity, Inventory Intensity do not have a significant effect on Tax Aggressiveness